Root development in Hevea brasiliensis in relation to management practices - Samarappuli L; Karunadasa P; Mitrasena U; Yogaratnam N (Journal of the Rubber Research Institute of Sri Lanka, 1996)
Feeder root density was shown to be significantly different between distances from the base of the rubber plant and in their vertical distribution with the highest percentage of roots being in the surface soil layers, 0-10 cm and 10-20 cm in the region of 120 cm circle. The amount of feeder roots in the surface soil was more than 75;of the total feeder roots and only 17.2;and 1.9;of the total root weights were found in the lower soil layers, 20-50 cm and 50-90 cm, respectively. Statistical calculations (coefficient of variation) of volumetric moisture content data indicated that the distance 60 cm from the tree at surface soil layers would appear to give the highest variation. Significant positive correlations were found between fine sand content (< 200m diameter) and root density, while clay content was nagatively correlated to root density. Root density had the tendency to decrease with increasing soil bulk density, but to increase with increasing soil organic carbon content. There was a significant difference in root density between clones. Vigorous clones like RRIC 102, RRIC 121, RRIC 100 and RRIC 110 had more feeder roots than a less vigorous clone like PB 86. Feeder root development also significantly differed between different establishment practices. Differences in the development of feeder roots were also shown to be significant with different soil moisture levels and potassium levels. Moreover, data obtained show that there was more vigorous feeder root development under mulching than under legume cover or natural cover.
Keywords: Hevea brasiliensis; Root development